Anterior Cervical Discectomy and Fusion by Using Bone Graft and Plate Versus Using Zero Size Peek Cage Filled with Bone Graft and Inbuilt Screws - Shahid Nawaz, Sarah Rehman, Saqib Khalil, Sanaullah Pathan, Abdul Rauf Memon, Mubarak Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to compare the clinical and radiological results of employing local bone graft with a PEEK cage vs bone graft and plate in ACDF. Study Design: Retrospective study Place and Duration: Department of Neurosurgery, Gomal Medical College DI Khan in the period from June, 2022 to November, 2022. Methods: There were 80 cases of both genders were included for anterior cervical discectomy and fusion. Detailed demographic information on enrolled cases was recorded after receiving informed written consent. Patients were divided in two groups. Group I received ACDF by using bone graft and plate in 40 cases while in 40 cases of group II ACDF was performed by using zero size peek cage filled with bone graft and inbuilt screws. Outcomes among both groups were compared. SPSS 22.0 was used to analyze all data. Results: Among 80 cases, there were 46 (57.5%) males and 34 (42.5%) females. Mean age of the patients was 43±18 years. Perioperative mean pain score was 7.5±6.20, mean NDI was 62.4±2.8, mean SF-36 was 29.8±3.15 in group I and in group II mean pain score was 6.9±5.20, NDI was 64.8±3.10 and SF-36 was 30.5±4.13. Significantly reduction in pain score, NDI and increase in SF-36 among both groups were found while in group II outcomes were better than group I. Mean operative time in group I was higher as compared to group II with p value <0.004. There was no any significantly difference in blood loss among both groups. With a p value of 0.003, group II had higher disc space height and segmental interbody angle at the operative segment than group I. Perioperative complication rates in group I was higher with p value <0.05. Conclusion: In this study, we found that patients undergoing ACDF with local bone graft and a PEEK cage had significantly shorter operating times, fewer perioperative problems, and better radiological outcomes than patients undergoing ACDF with bone graft and plate. A PEEK cage-encased local bone graft seems to be a secure substitute for an ACDF's bone transplant. Keywords: Cervical spine, Anterior cervical discectomy and fusion, bone graft, Local bone graft